2004
DOI: 10.1128/jvi.78.21.11926-11938.2004
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Transcription Factor Nrf-2 and Its Downstream Targets in Response to Moloney Murine Leukemia Virusts1-Induced Thiol Depletion and Oxidative Stress in Astrocytes

Abstract: The neuroimmunodegenerative syndrome that develops in mice infected with ts1, a mutant of Moloney murine leukemia virus, resembles human AIDS. Both ts1 and human immunodeficiency virus type 1 infect astrocytes, microglia, and oligodendrocytes but do not infect neurons. Oxidative stress has been implicated in the neuropathology of AIDS dementia and other neurodegenerative diseases. We report here that ts1 infection of astrocytes (both transformed C1 cells and primary cultures) also induces thiol (i.e., glutathi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
101
1
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(106 citation statements)
references
References 82 publications
(124 reference statements)
3
101
1
1
Order By: Relevance
“…We observed that HCV infection can induce and translocate Nrf2 in a time-dependent manner, and demonstrated further that HCV-induced Nrf2 activation is sensitive to antioxidants and Ca 2+ chelators. This is consistent with previous observations that, in response to virus infection, activation of Nrf2 occurs under conditions of oxidative stress (Qiang et al, 2004;Jiang et al, 2006).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…We observed that HCV infection can induce and translocate Nrf2 in a time-dependent manner, and demonstrated further that HCV-induced Nrf2 activation is sensitive to antioxidants and Ca 2+ chelators. This is consistent with previous observations that, in response to virus infection, activation of Nrf2 occurs under conditions of oxidative stress (Qiang et al, 2004;Jiang et al, 2006).…”
Section: Discussionsupporting
confidence: 82%
“…Recently, it has been shown that upregulation of Nrf2 in lung cancer cells stimulated growth of lung cancerderived cell lines (Padmanabhan et al, 2006;Ohta et al, 2008). Previous studies have demonstrated that Nrf2 in Moloney murine leukemia virus ts1-infected astrocytes was activated in response to thiol depletion and oxidative stress (Qiang et al, 2004). Oxidative and electrophilic stresses are the major stimuli that provoke the induction of Nrf2 target genes (Ohta et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…22,38 Here, we have shown that levels of ER stress markers, GRP78 and cleavage of procaspase-12 were also increased in Atm À/À astrocytes (Figure 3a).…”
Section: Atm-deficient Astrocytes Show Signs Of Oxidative Stress and mentioning
confidence: 88%
“…Recent studies indicate that Syncytin-1 transcript levels are quantitatively increased in the brains of MS patients compared with other inflammatory neurological disease controls (10). Interestingly, TNF-␣, an inflammatory molecule in the brains of MS patients, was found to enhance Syncytin-1 expression in astrocytes (11), which consequently results in production of free radicals and cytokines (12) that could affect expression of ASCT1 and ASCT2, given that free radicals influence expression of membrane proteins (13,14). Free radicals are also produced when cells undergo persistent endoplasmic reticulum (ER) stress (15), a constellation of host responses, which maintain cellular homeostasis, termed the unfolded protein response (16).…”
Section: Ultiple Sclerosis (Ms)mentioning
confidence: 99%